2003
DOI: 10.1007/s11738-003-0001-8
|View full text |Cite
|
Sign up to set email alerts
|

Isozymes variability among Fusarium udum resistant cultivars of pigeonpea (Cajanus cajan (L.) (Millsp)

Abstract: The present study was carried out to select the different pigeonpea cultivars for resistance against wilt caused by Fusarium udum and to assess the genetic variability among the resistant and susceptible cultivars. These cultivars were screened by root dip inoculation and classified into resistant (ICP 8863 and 9145), moderately resistant (ICP 11681 and Selection-1), susceptible (ICP 7118, TRG-1 and LRG-30) and highly susceptible cultivars (1CP-2376 and LRG-41). The peroxidase activity (PEO) in both leaf and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Several studies have investigated alterations in isozyme patterns in plants infected with different pathogens. Prasad et al (2003) analyzed isozyme variability among Fusarium udum resistant cultivars of pigeon pea (Cajanus cajan L.). They concluded that the polymorphisms observed among isozymes such as peroxidases, phosphatases and esterases may be helpful in the characterization of resistance and susceptibility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have investigated alterations in isozyme patterns in plants infected with different pathogens. Prasad et al (2003) analyzed isozyme variability among Fusarium udum resistant cultivars of pigeon pea (Cajanus cajan L.). They concluded that the polymorphisms observed among isozymes such as peroxidases, phosphatases and esterases may be helpful in the characterization of resistance and susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…Isozymes, peroxidase, polyphenol oxidase, superoxide dismutase, and pathogenesis-related proteins, such as chitinase and β-1,3-glucanase, have very important roles in resistance to plant pathogenic fungi (Prasad et al, 2003). Natural resistance is genetically controlled, and resistance genes are expressed through the production of biological products such as secondary metabolites, including phenolics, lignin, suberin, phytoalexins, alkaloids, terpenes, glycosides, degrading enzymes, and pathogenesis-related proteins, all of which contribute to disease resistance (Gupta et al, 2010).…”
mentioning
confidence: 99%
“…Fusarium wilt (FW) caused by Fusarium udum is an important biotic constraint in pigeonpea production in the Indian subcontinent, which results in 16-47% crop losses [ 5 ]. The fungus enters the host vascular system at the root tips through wounds or invasion made by nematodes, leading to progressive chlorosis of leaves, branches, wilting and collapse of the root system [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Yield losses of wilt susceptible crops ranged from 16 to 47% (Prasad et al, 2003) or even 100% (Reddy et al, 1990) causing losses up to 71 million US $ annually in India alone (Reddy et al, 1993). Wilt symptoms usually appear during flowering and pod stage of the crop.…”
Section: Introductionmentioning
confidence: 99%